Supplementation of a polyherbal phytogenic in finishing lamb’s feedlot rations - Sánchez-Torres , María Teresa; Cordero-Mora, Jos Luis; MARTINEZ AISPURO, JOSE ALFREDO; Mendoza- Martínez, German David; Ayala-Monter, Marco Antonio; Vázquez-Silva , Gabriela; Hernández-García , Pedro Abel; Figueroa-Velasco, José Luis (Ecosistemas y Recursos Agropecuarios, 2022)
The aim was to evaluate the effect of dietary addition of a polyherbal phytogenic (Animunin) on the productive performance and blood biochemistry in finishing lambs. Forty Hampshire × Suffolk males lambs (initial body weight 26.52 ± 2.13 kg) were allocated according to a completely randomized design in four treatments. Treatments consisted of dietary inclusion of the Animunin at 0, 1, 2, and 3 g kg−1 dry matter (DM). Animunin addition was not modified (p > 0.05) the productive performance, DM intake, backfat thickness, chop area, energy and protein metabolites, or liver enzymes. While hematocrit, hemoglobin and erythrocytes showed a quadratic response (p ≤ 0.05) with Animunin. The polyherbal phytogenic evaluated did not improve lamb’s productive performance and metabolites related with immune response.